Engineering Characteristics of Khon Kaen Loess as Construction Material - Apichit Kampala (International Association of Lowland Technology, 2020)
In Khon Kaen province, the northeast of Thailand, the soil layer consists mostly of silty sand and silty clay with fine soil grains. This soil is a wind-blown deposit into layers of soil and is named “Loess” or “Khon Kaen Loess”. Thus far, there has been a limited studies conducted on its engineering properties and the use of this soil is also limited. Accordingly, this research studied the improvement of the basic and engineering properties of this Loess with addition of clay. The results indicated that Loess can be classified as inactive -silty-sandy clay. The yield stress of Loess-clay decreased with the increasing amount of clay and was directly related to the compressive strength. The compression index and swelling index also decreased with increasing consistency index. The ratio of is significantly correlated with the coefficient of compressibility and permeability coefficient. Still, the effective cohesion of Loess is relatively low (approximately 20 kPa) and it will not change with the clay amount. The maximum of the effective internal friction angle is 25 degrees while the soaked bearing strength seems to decrease following the increasing amount of clay. Notably, the basic and engineering parameters of Khon Kaen loess are mutually connected via an experiential relationship whereas the predicted outcomes and the results from other studies are similar. The experiential equation from this research could be used to predict the engineering properties of silty soil or other types of low-swelling clay.